‘I Wasn’t Born with Enough Middle Fingers’: How low-budget horror films defy sexual m orality and heteronormativity in Bollywood - Sen, Aditi (Acta Orientalia Vilnensia, 2011)
Queen’s University In the early 1980s the Ramsay Brothers gave Bollywood a new genre of monster flicks with blockbusters like Purana Mandir, Hotel, and Veerana. Following the work of the Ramsay Brothers, low-budget horror films that were made exclusively for the small towns and rural market increased in the decades of 1980s and 1990s. These films are primarily known for their unintentional humor owing to poor production and acting, but they have never been acknowledged for their actual content. This article argues that Bollywood low-budget films fulfilled the basic function of horror movies—that is, they subverted mainstream moral order and sexual morality. These films opened up space for dialogues that the mainstream cinema had totally neglected; particularly, in the areas of incest, female lust, ‘othering’ of male sexuality, and transgendered identities. On a different register, the relationship between low-budget horror films and mainstream Bollywood can be compared to folklore and canonical literature, where folklore repeatedly resists the conformities endorsed by the mainstream prescriptive texts.